Did ETS Coverage and Free Allowances Affect Economic Performance and GHG Emissions in the EU?: Evidence from a Panel of EU Sectors - Aydin, Asli; Acar, Sevil (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2025)
This study analyzes the impacts of the European Union Emissions Trading System and free allowances on sectoral value added, gross output, and greenhouse gas emissions in the European Union for the period 1995-2020. Since the European Union Emissions Trading System inherently covers firm-level emissions, most studies in this area have been conducted at the firm level. However, a sectoral analysis allows understanding how sectors as a whole respond to the carbon pricing mechanism in terms of carbon reductions, competitiveness and sectoral output growth. It can also reveal how changes differ across sectors subject to different regulations. Controlling for sectoral employment, intermediate input use, and time effects, the results show that European Union Emissions Trading System coverage has a negative impact on both value added and gross output, but does not lead to a significant reduction in greenhouse gas emissions. The findings indicate that more labor-intensive and less input-intensive production can reduce emissions. Furthermore, the study draws attention to the competitive losses caused by compliance costs in sectors within the scope of the European Union Emissions Trading System and shows that the impact of free allowances on performance is insufficient. These results highlight the importance of coherent and inclusive approaches in policy design to more effectively manage the economic and environmental impacts of the European Union Emissions Trading System. It is recommended to develop more targeted and flexible strategies, taking into account sectoral differences.